Determinants of the Composite Stock Price Index (JCI) on the Indonesia Stock Exchange (IDX) Based on the Nikkei Stock Exchange 225 Index (N225), Brent Crude Oil Price, and Rupiah Exchange Rate for the Period 2020-2023 - Nugroho, Titan Baihaqi Akbar; Dwiridotjahjono, Jojok (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The movement of the Indonesia Composite Stock Price Index (JCI) on the Indonesia Stock Exchange (IDX) is influenced by various domestic and global factors. This study aims to analyze the impact of the Nikkei 225 Index, Brent Crude Oil Prices, and the Rupiah Exchange Rate on JCI during the period 2020-2023. The research adopts a quantitative approach by employing multiple linear regression analysis to process secondary data obtained from Investing.com and Bank Indonesia. The findings indicate that, simultaneously, the three independent variables significantly influence JCI movements. However, when analyzed individually, the Nikkei 225 Index and Brent Crude Oil Prices exert a positive and significant effect on JCI, whereas the Rupiah Exchange Rate does not show a substantial impact. These results suggest that JCI fluctuations are more responsive to global economic changes than to domestic monetary dynamics. The implications of this study highlight the necessity for investors to consider international market conditions as a crucial factor when making investment decisions on the Indonesian stock market. This research contributes to the existing body of literature by providing empirical evidence on the relationship between global and domestic economic indicators and JCI, particularly in the post-pandemic period. The originality of this study lies in its focus on recent economic conditions, offering valuable insights for policymakers, investors, and financial analysts. By addressing the influence of global market trends on JCI, this research underscores the importance of macroeconomic awareness in investment strategies and economic policymaking.